ANALYSIS ON INTERNATIONAL SECURITY POLICY THROUGH THE PRISM OF THE 52ND MUNICH SECURITY CONFERENCES (Annual of the Faculty of Philosophy in Skopje, 2016)
Conducted a comprehensive analysis of the Munich Security Conference on which participation in discussions taking high representatives of states and international organizations. As a leadership forum in the international community is trying to offer practical solutions and initiatives for solving the issues in international relations with a special emphasis on security challenges and threats of the 21st century. At the 52nd Munich Security Conference main topics of discussions were about the problems of the crisis in the European security system, the war in Syria, global activities of terrorist groups, refugee crisis and the security implications of global climate change and disease. Also at the security conference were offered various ideas for dealing with the new challenges, risks and threats, as well as assistance for the countries of the crisis regions.
Keywords: MUNICH SECURITY CONFERENCE; INTERNATIONAL ACTORS; CRISIS REGIONS; SECURITY CHALLENGES